PENGARUH PERCEIVED WAITING TIME DAN SATISFACTION WITH WAITING ENVIRONMENT TERHADAP SERVICE SATISFACTION DI RESTORAN XSURABAYA - Bian Pagudisaputra; Siti Rahayu; Fitri Novika Widjaja (Perpustakaan Universitas Surabaya, 2018)
This research was conducted to determine the effect of perceived waiting time andsatisfaction with waiting environment on waiting time satisfaction and service satisfaction in X restaurant Surabaya. Descriptive analysis along with Partial Least Square is used in this research. The result shows there is a positive significant effect between perceived waiting time and waiting time satisfaction also from waiting time satisfaction and service satisfaction, and also a positive but not significant effect from satisfaction with waiting environment and waiting time satisfaction also from satisfaction with waiting environment and service satisfaction. It also found a negative but not significant effect from perceived waiting time and service satisfaction.